Transcutaneous auricular vagus nerve immediate stimulation treatment for treatment-resistant depression: A functional magnetic resonance imaging study - Ma, Yue; Wang, Zhi; He, Jiakai; Sun, Jifei; Guo, Chunlei; Du, Zhongming; Chen, Limei; Luo, Yi; Gao, Deqiang; Hong, Yang; Zhang, Lei; Liu, Yong; et al. (Frontiers in Neurology, 2022)
Objective: Transcutaneous auricular vagus nerve stimulation (taVNS) has been reported to be effective for treatment-resistant depression (TRD). To observe the immediate modulating effect of taVNS brain activity in patients with TRD by rest-state functional magnetic resonance imaging (rs-fMRI). Method:Forty patients with TRD, Forty healthy control (HC) were included in rs-fMRI scans. rs-fMRI was performed before and after 30 min taVNS at baseline.Amplitude of low-frequency fluctuations (ALFF),Fractional amplitude of low-frequency fluctuations (fALFF) and regional homogeneity (ReHo) indexes were used for image analysis. Results：ANOVA analysis revealed significant group×time interactions on ALFF and ReHo were observed in the right medial orbital frontal cortex(mOFC).There are no significant changes found in fALFF.Post hoc showed taVNS aroused higher activation in the HC group than baseline in ALFF (t=3.635 , P< 0.001). Post hoc analysis also revealed that the ReHo was significantly decreased in the OFC of patients with TRD(t=-4.213 , P <0.001) and the value of TRD group was significantly lower than HC group after stimulation(t=-2.661 , P =0.009) . Conclusion:taVNS can immediately regulate the spontaneous brain activity of TRD patients. This study found that TRD has abnormal neural activity in the OFC brain area, which involves emotional cognition and reward circuits. It was speculated that OFC is a potential targeting brain region of taVNS intervention.